Assessment of chemical and organoleptic properties of fortified indigenous maize-based snack (2019)
Backgronnd: Aadun is an indigenous maize-bascd snack high in energy, phosphorus and magnesium but low in protein. it is often sold with minimal packaging under conditions which may lead to its rapid deterioration. Protein fortification and improved packaging could enhance its balance of nutrients and increase acceptability. Objective: The study evaluated the chemical composition and organoleptic qualities of fortified, aadun. Methodology: Four different samples of aadun were prepared. T0 served as the control (unfortified aadun) while the three others (T i, T2 and T3 were fortified with groundnut, cray fish and soybeans, respectively. The four samples were subjected to proximate and mineral analysis. Different packaging materials such as foil paper, polyethylene and plastic plate covered with kiln film were used to present the samples to 50 panellists for organoleptic assessment. Results were subjected to descriptive statistics and ANOV A using SPSS version 20 Results- fortified samples were found to be significantly different in their chemical composition and sensory attributes from the control sample. The fortified aadun samples had higher protein, crude fibre, ether extract, iron magnesium, iodine, sodium, potassium and phosphorus due the control. The T0, was rated highest for the colour and the T1 for taste, texture, aroma and overall acceptability. The most preferred packaging material for the samples was plastic plate covered with kiln film while polyethylene was least preffered. Conclusion: Fortifying aadun with different ingredients especially groundnut and improving the materials used in packaging will improve its consumer acceptability.